Implementasi Khitbah Berbasis Takzim pada Pesantren Salafiyah Syafiiyah Asyhariyah Curahlele Balung Jember - Muhammad Ali Wafa (Rechtenstudent, 2021)
The pre-wedding process such as the true sermon should not escape the seriousness of the bride and groom. One form of seriousness is to ask for advice and even the involvement of local religious leaders, as was done by students at the Salafiyah Syafiiyah Islamic Boarding School Asyhariyah Curahlele, Balung, Jember. The reason for the students is not only looking for blessings, but also a form of reverence for Kiai. The uniqueness of the khitbah system based on reverence for the Kiai at the Islamic Boarding School needs to be studied based on Islamic law to get the essence of the concept, so that it is clear then the law of its implementation. By using field research, it was found that the khitbah system at the Salafiyah Syafiiyah Islamic Boarding School Asyhariyah Curahlele, Balung, Jember is a form of voluntary reverence. Based on the caregivers and alumni of the Pondok, it was found that the Kiai's role was passive in carrying out the sermon at the Salafiyah Syafiiyah Asyhariyah Islamic Boarding School. That is, the kiai places himself as an intermediary between the preacher and those who will be preached and does not intervene and even force his students to accept their opinion. Based on this explanation, the practice of khitbah with the intermediary of a Kiai does not violate Islamic law. Islam itself stipulates that it is permissible for sermons to be carried out using intermediaries, so that the Kiai's involvement in this matter is legal according to Islamic law, because the Kiai is the intermediary. The reason for the santri receiving the khitbah for reasons of reverence for the Kiai is that it is permissible, because what is a valid requirement is the approval of the candidate and the candidate's family, related reasons have never been included in Islam.